Impacts of public procurement on business R&D efforts: The Brazilian case - Andre Tortato Rauen; Bianca Souza de Paiva (Institute for Applied Economic Research (ipea), 2019)
This paper aims to evaluate the impact of federal public procurement on business R&D efforts in the 2013-2016 period regardless of the participation in any public procurement program (PPI). We conducted a quasi-experiment (with propensity score matching) in which we compared firms that sold to the federal government with firms that did not. To understand the differences between the type of procurer and type of procured goods and services, we conducted five exercises: general sample; contracts from the Ministry of Health, Ministry of Education and, Ministry of Defense, and with only high-tech suppliers. Regardless of the sample type, there was no impact on public procurement on the technology efforts of suppliers (considering the technology intensity approach). However, we found an unexpected impact on suppliers' total personnel (PO). Our results show that to produce some positive results on technological R&D, public procurement should be specifically designed to do that. In other words, without a strong PPI program, there will be no positive outcome in terms of technology development. Public procurement works as an innovation policy tool but must be designed to do so.
Keywords: H57; O32; O38; 330; public procurement for innovation; quasi-experiment; Brazil